( 2 3 + 1 ) ( 3 3 + 1 ) ( 4 3 + 1 ) ⋯ ( 1 0 0 0 3 + 1 ) ( 2 3 − 1 ) ( 3 3 − 1 ) ( 4 3 − 1 ) ⋯ ( 1 0 0 0 3 − 1 ) = ?
Submit your answer to three decimal places.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Sir how have you changed ( n 2 − n + 1 ) to ( n 2 + n + 1 ) ??? Thank you
Log in to reply
Note that n 2 − n + 1 = ( n − 1 ) 2 + ( n − 1 ) + 1 , so
n = 2 ∏ 1 0 0 0 ( n 2 − n + 1 ) = n = 2 ∏ 1 0 0 0 ( ( n − 1 ) 2 + ( n − 1 ) + 1 ) = k = 1 ∏ 9 9 9 ( k 2 + k + 1 ) ,
where k = n − 1 goes from 1 to 9 9 9 as n goes from 2 to 1 0 0 0 .
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Telescoping Series - Product
P = n = 2 ∏ 1 0 0 0 n 3 + 1 n 3 − 1 = n = 2 ∏ 1 0 0 0 ( n + 1 ) ( n 2 − n + 1 ) ( n − 1 ) ( n 2 + n + 1 ) = ∏ n = 2 1 0 0 0 ( n + 1 ) ∏ n = 2 1 0 0 0 ( n 2 − n + 1 ) ∏ n = 2 1 0 0 0 ( n − 1 ) ∏ n = 2 1 0 0 0 ( n 2 + n + 1 ) Note that ( n + 1 ) 2 − ( n + 1 ) + 1 = n 2 + n + 1 = ∏ n = 3 1 0 0 1 n ∏ n = 1 9 9 9 ( n 2 + n + 1 ) ∏ n = 1 9 9 9 n ∏ n = 2 1 0 0 0 ( n 2 + n + 1 ) = 1 0 0 0 ⋅ 1 0 0 1 ⋅ 3 2 ⋅ 1 0 0 1 0 0 1 = 5 0 0 5 0 0 3 3 3 6 6 7 ≈ 0 . 6 6 7